Study Guide for Sociology - Jean Stockard (Wadsworth, 2000)
Includes 20 study questions per chapter, concept application and applied research sections, Practice Quizzes with answers so that students can assess their own progress, a continuing education section features films, further reading, Internet resources and InfoTrac exercises